1998
DOI: 10.1093/humrep/13.9.2612
|View full text |Cite
|
Sign up to set email alerts
|

Circulating concentrations of placenta protein 14 during the natural menstrual cycle in women significantly reflect endometrial receptivity to implantation and pregnancy during successive assisted reproduction cycles

Abstract: Placenta protein 14 (PP14), which is the most abundant product of the secretory endometrium, has been proposed as the best biochemical marker of endometrial function in women. In this study, 19 normogonadotrophic women of infertile couples were monitored with serial measurements of concentrations of PP14, gonadotrophins and sex steroids and ultrasound scanning of endometrial thickness throughout three consecutive cycles. The first two of these were natural, unstimulated cycles (cycles 1 and 2), while ovarian s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
21
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 17 publications
2
21
1
Order By: Relevance
“…Consistently, they showed that galectin-9 mRNA was expressed at very low concentrations during the proliferative and early secretory phases but showed a sharp and significant increase in the mid-secretory phase [14]. Thus, galectin-9 can be considered as one of the very few epithelial markers, such as glycodelin (PP14) [22], that are strictly regulated during the menstrual cycle. A sharp and strong expression of galectin-9 during the window of implantation suggests a potential role of this lectin during embryo implantation.…”
Section: Discussionmentioning
confidence: 76%
“…Consistently, they showed that galectin-9 mRNA was expressed at very low concentrations during the proliferative and early secretory phases but showed a sharp and significant increase in the mid-secretory phase [14]. Thus, galectin-9 can be considered as one of the very few epithelial markers, such as glycodelin (PP14) [22], that are strictly regulated during the menstrual cycle. A sharp and strong expression of galectin-9 during the window of implantation suggests a potential role of this lectin during embryo implantation.…”
Section: Discussionmentioning
confidence: 76%
“…Available evidence from humans, laboratory animals, and domestic animals indicates that a reduction in uterine histotroph compromises periimplantation conceptus survival and growth, which can lead to infertility and intrauterine growth retardation (9,11,12). Recent studies correlate inadequate expression of cellsurface and secretory proteins with retarded endometrial differentiation and defective endometrial secretory phases (13)(14)(15). Therefore, identification of useful molecular and cellular markers of endometrial function and receptivity to the conceptus are of utmost importance, because they can be used for evaluation, regulation, and enhancement of fertility (15).…”
mentioning
confidence: 99%
“…Recent studies correlate inadequate expression of cellsurface and secretory proteins with retarded endometrial differentiation and defective endometrial secretory phases (13)(14)(15). Therefore, identification of useful molecular and cellular markers of endometrial function and receptivity to the conceptus are of utmost importance, because they can be used for evaluation, regulation, and enhancement of fertility (15).…”
mentioning
confidence: 99%
“…PP14 also inhibits Natural Killer cell activity (16). That the protein is essential for normal pregnancy progression has been established by the association of low levels of PP14 with habitual abortion (17,18), unexplained infertility (19), and establishment of pregnancy in women during those cycles in which normal concentrations of PP14 were detected (20). Despite the growing literature on the multifunctional role of PP14, the mechanism of action of this protein has not been delineated at the molecular level.…”
mentioning
confidence: 99%